2022
DOI: 10.1002/cbic.202200098
|View full text |Cite
|
Sign up to set email alerts
|

Claisen Condensation Reaction Mediated Pimelate Biosynthesis via the Reverse Adipate‐Degradation Pathway and Its Isoenzymes

Abstract: Pimelic acid is an important seven‐carbon dicarboxylic acid, which is broadly applied in various fields. The industrial production of pimelic acid is mainly through a chemical method, which is complicated and environmentally unfriendly. Herein, we found that pimelic acid could be biosynthesized by the reverse adipate‐degradation pathway (RADP), a typical Claisen condensation reaction that could be applied to the arrangement of C−C bond. In order to strengthen the supply of glutaryl‐CoA precursor, PA5530 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Biotechnological applications benefit from highly active and thermostable enzymes to perform catalysis effectively and economically. , In our previous study, Thermobifida fusca β-ketothiolase Tfu_0875 exhibited excellent catalytic properties for the biosynthesis of dicarboxylic acids. Herein, we demonstrated that Tfu_0875 possesses high thermostability and enzyme activity. In order to rationally design the substrate tunnel of Tfu_0875 to further improve enzyme activity, we applied the deep learning approach (DLKcat) to predict k cat values based on the high-resolution three-dimensional (3D) protein structure .…”
Section: Introductionmentioning
confidence: 80%
“…Biotechnological applications benefit from highly active and thermostable enzymes to perform catalysis effectively and economically. , In our previous study, Thermobifida fusca β-ketothiolase Tfu_0875 exhibited excellent catalytic properties for the biosynthesis of dicarboxylic acids. Herein, we demonstrated that Tfu_0875 possesses high thermostability and enzyme activity. In order to rationally design the substrate tunnel of Tfu_0875 to further improve enzyme activity, we applied the deep learning approach (DLKcat) to predict k cat values based on the high-resolution three-dimensional (3D) protein structure .…”
Section: Introductionmentioning
confidence: 80%
“…Tfu_0875 belongs to the thiolase I which prefers medium-chain length substrates [ 8 ]. Therefore, we selected acetyl-CoA, malonyl-CoA, succinyl-CoA, and glutaryl-CoA as substrates to condensation with an extension unit acetyl-CoA by Tfu_0875 for evaluating the substrate specificity [ [14] , [15] , [16] ]. As a result, Tfu_0875 demonstrated a relatively broad substrate range, spanning from C2 to C5 carbon chain lengths.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we developed a reverse adipate degradation pathway (RADP) for the production of dicarboxylic acids, including glutaric acid [ 14 ], adipic acid [ 15 ], and pimelic acid [ 16 ], which play an important role as biofuels [ 11 ] and nylon monomers 9 . The 3-ketoacyl-CoA thiolase, a member of the thiolase I family, serves as the initial and rate-limiting enzyme in the RADP pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield of adipic acid reached 2.50 g/L in a controlled bioreactor with a high initial glycerol concentration. Recently, Bao et al 100 also achieved a high concentration of pimelic acid (36.7 mg/L) using the Claisen condensation reaction. This was accomplished by adopting glutaryl coenzyme A as a precursor and expressing RADP and BioZ pathway isoenzymes in E. coli.…”
Section: Claisen Condensation Reaction and Carbon Chain Derivationmentioning
confidence: 99%